Fatigue Crack Initiation Change of Cast AZ91 Magnesium Alloy from Low to Very High Cycle Fatigue Region - Stanislava Fintová (MDPI AG, 2021)
Fatigue tests were performed on the AZ91 cast alloy to identify the mechanisms of the fatigue crack initiation. In different fatigue regions, different mechanisms were observed. In the low and high cycle fatigue regions, slip markings formation accompanied with Mg17Al12 particles cracking were observed. Slip markings act as the fatigue crack initiation sites. The size and number of slip markings decreased with decreased stress amplitude applied. When slip markings formation was suppressed due to low stress amplitude, particle cracking became more important and the cracks continued to grow through the particle/solid solution interface. The change of the fatigue crack initiation mechanisms led the S-N curve to shift to the higher number of cycles to the fracture, demonstrated by its stepwise character. A lower fatigue limit of 60 MPa was determined at 20 kHz for 2 × 109 cycles compared to the 80 MPa determined at 60 Hz for 1 × 107 cycles.